2012
DOI: 10.2105/ajph.2011.300557
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Natural Cold and Heat: Hypothermia and Hyperthermia Medicare Claims, United States, 2004–2005

Abstract: This study highlighted the magnitude of these preventable conditions among older adults and disabled persons and the burden on the Medicare system. These results can help target public education and preparedness activities for extreme weather events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 20 publications
1
29
0
Order By: Relevance
“…Individual racial and ethnic identity is often strongly associated with heat-associated morbidity and mortality in the U.S. For example, blacks have often been found to have increased vulnerability [11, 21, 45-51, 52] and Asians have been found to have decreased vulnerability [49]. However, some studies have not found race or ethnicity to be associated with heat-associated health effects [53-55], and in a study of high temperatures and emergency room visits for various cardio-respiratory diseases in California, as compared to whites, risks were higher among Hispanics for some diseases and lower among blacks, Hispanics or Asians for others [56].…”
Section: Race/ethnicitymentioning
confidence: 99%
“…Individual racial and ethnic identity is often strongly associated with heat-associated morbidity and mortality in the U.S. For example, blacks have often been found to have increased vulnerability [11, 21, 45-51, 52] and Asians have been found to have decreased vulnerability [49]. However, some studies have not found race or ethnicity to be associated with heat-associated health effects [53-55], and in a study of high temperatures and emergency room visits for various cardio-respiratory diseases in California, as compared to whites, risks were higher among Hispanics for some diseases and lower among blacks, Hispanics or Asians for others [56].…”
Section: Race/ethnicitymentioning
confidence: 99%
“…Age has been found to modify the association between EH and mortality, with EH effects greater among individuals at least 65 years old (Basu 2009). Some U.S. studies have suggested increased vulnerability by racial and ethnic characteristics, with increased vulnerability among non-whites or blacks (Fletcher et al 2012, Lin et al 2009, Medina-Ramon et al 2006, Noe et al 2012, O’Neill et al 2003, Schwartz 2005, Ye et al 2012, Zanobetti et al 2013) and decreased vulnerability among Asians (Noe et al 2012), while other studies have not found increased vulnerability by racial and ethnic characteristics (Green et al 2010, Pillai et al 2014). Beyond individual racial effects, there may be neighborhood-level effects of living in a community of racial minorities(Morenoff and Lynch 2004), where resources and information for coping with EH may be further limited as a result of present and historical racial segregation.…”
Section: Introductionmentioning
confidence: 99%
“…From 2001 to 2004, HRI was the most frequent cause of environmental exposure-related injury treated in emergency departments (EDs) across the U.S. [6], while annual Medicare claims for hyperthermia treated in EDs have been estimated at over $36 million [7]. HRI ranges in severity from mild cramps to heat exhaustion to heat stroke, and can quickly progress across this spectrum if treatment is not provided [8].…”
Section: Introductionmentioning
confidence: 99%